Market Orientation of Women Dairy Farmers of Kerala - Reeja George Pulinilkunnathil (Journal of Extension Education, 2020)
The study explores the status of women dairy farmers of Kerala state with respect to marketing variables that have a significant effect on their entrepreneurial behavior. The variables studied include the extent of utilization of marketing facilities, credit orientation and competition orientation. The study was conducted among 153 women dairy farmers, selected through the process of multistage random sampling from Ernakulam, Palakkad, and Thrissur districts of the state. Sharp contrasts with regard to the level of market utilization was observed among farmers with different herd sizes, while higher levels of market utilization were observed among around sixty percent of respondents with larger herd size. None of the respondents with small herd size had high level market facilities utilization. Extent of utilization of market facilities was positively and significantly associated with entrepreneurial behavior of the respondents. Similarly, respondents with larger herd sizes had significantly higher competition orientation scores when compared to those with smaller herd sizes. Most of the respondents in this study fell in the medium level of credit orientation. However, non-significant correlation was observed between credit orientation and entrepreneurial behavior. None of the respondents with more than two cows had low level of competition orientation. Most of the respondents fell in the medium level of competition orientation. Competition orientation was positively and significantly correlated with entrepreneurial behavior of the respondents.